1990
DOI: 10.1159/000243256
|View full text |Cite
|
Sign up to set email alerts
|

An Explanation for Ketogenesis by the Intestine of the Suckling Rat: The Presence of an Active Hydroxymethylglutaryl-Coenzyme A Pathway

Abstract: Hydroxymethylglutaryl-coenzyme A (HMG-CoA) synthase is present in the mucosa of the proximal small intestine of the suckling rat, as are acetoacetyl-CoA thiolase and HMG-CoA lyase. At weaning the activity of HMG-CoA synthase decreases by 90%. This change in activity parallels a change in the rate of ketogenesis in vitro by mucosal scrapings. Starvation of the pups decreases the rate of ketogenesis. It is concluded that the mucosa of the developing rat has an active HMG-CoA pathway and that there may be a relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In the small intestine mHMGCS instead has a food intake related expression . It has previously been shown to be highly expressed in the early postnatal period in suckling rodents, and starvation decreased its expression, in opposition to hepatic ketogenesis 19 20. After weaning to LFD the expression disappeared from the intestine 20.…”
Section: Discussionmentioning
confidence: 94%
“…In the small intestine mHMGCS instead has a food intake related expression . It has previously been shown to be highly expressed in the early postnatal period in suckling rodents, and starvation decreased its expression, in opposition to hepatic ketogenesis 19 20. After weaning to LFD the expression disappeared from the intestine 20.…”
Section: Discussionmentioning
confidence: 94%
“…This would explain the normal ketone levels observed in the starved mice with proximal tubular cell specific Atg5 deletion. In addition, it has been reported that intestinal cells have ketogenic genes 25 26 , suggesting they can produce ketone bodies. Further experiments examining these possibilities could provide additional insights into the physiology of starvation.…”
Section: Discussionmentioning
confidence: 99%
“…After lactation ends, the long chain fatty acids and the small amount of MCFA stored in adipose tissue provide the substrate to prolong mild ketonemia for many months. Incidentally, in addition to the liver, the infant gut can also synthesize ketones ( Bekesi and Williamson, 1990 ).…”
Section: Ketones: Essential In Early Human Brain Developmentmentioning
confidence: 99%